Peunajoh Aceh as a Cultural Driver of Halal Tourism and Creative Economy - Zulfikar Zulfikar; Mira Chairani; Cut Santika (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Halal tourism has emerged as a significant global trend combining religious observance with cultural experience, positioning regions with strong Islamic traditions, such as Aceh, to play a strategic role. Specific Background: Within this context, Peunajoh Aceh—a traditional culinary and cultural practice rooted in Islamic and communal values—holds potential as an authentic symbol for promoting halal tourism and strengthening the local creative economy. Knowledge Gap: Despite its cultural richness, the role of Peunajoh Aceh in advancing halal tourism and supporting micro, small, and medium enterprises (MSMEs) has not been systematically examined. Aims: This study investigates how Peunajoh Aceh contributes to halal tourism promotion and its subsequent impact on the creative economy in Bireuen Regency, Aceh. Results: Using a mixed-methods approach involving policymakers, MSME actors, and tourists, findings reveal that Peunajoh Aceh significantly enhances halal tourism through culinary innovation, digital marketing, and community-based enterprise development, although challenges remain in certification access, managerial skills, and promotional integration. Novelty: The study uniquely links local tradition with economic innovation within the halal tourism framework. Implications: Strengthening cross-sector collaboration, digitalization, and halal certification accessibility is crucial for transforming Peunajoh Aceh into a sustainable cultural-economic driver and an authentic global icon of halal tourism. Highlights: Strengthens Aceh’s halal tourism through culture-based culinary innovation. Empowers MSMEs to enhance digital marketing and halal certification. Bridges tradition, religion, and economy for sustainable regional development. Keywords: Peunajoh Aceh, Halal Tourism, Creative Economy, MSMEs, Cultural Heritage